2017
DOI: 10.1038/srep46496
|View full text |Cite|
|
Sign up to set email alerts
|

Heat, temperature and Clausius inequality in a model for active Brownian particles

Abstract: Methods of stochastic thermodynamics and hydrodynamics are applied to a recently introduced model of active particles. The model consists of an overdamped particle subject to Gaussian coloured noise. Inspired by stochastic thermodynamics, we derive from the system’s Fokker-Planck equation the average exchanges of heat and work with the active bath and the associated entropy production. We show that a Clausius inequality holds, with the local (non-uniform) temperature of the active bath replacing the uniform te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
139
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(146 citation statements)
references
References 47 publications
7
139
0
Order By: Relevance
“…Recently it has been shown that the above fallacy is bypassed in a model of active particles where Gaussian colored noise plays the role of self-propulsion [19][20][21]. Even if thermal fluctuations are neglected, a notion of "coarse-grained heat" can be introduced, together with a spatial-dependent effective temperature, such that the original Clausius relation is fully recovered.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently it has been shown that the above fallacy is bypassed in a model of active particles where Gaussian colored noise plays the role of self-propulsion [19][20][21]. Even if thermal fluctuations are neglected, a notion of "coarse-grained heat" can be introduced, together with a spatial-dependent effective temperature, such that the original Clausius relation is fully recovered.…”
Section: Introductionmentioning
confidence: 99%
“…Based upon such a bare diffusivity, the "active bath temperature" T a = γD a is usually defined. In [21] a "mass-less" active temperature T τ = D a /τ was defined. In this paper we show that it is not necessary, if an "effective mass" µ = γτ is used, as in [23].…”
Section: Active Particles: the Coarse-grained Heat And Clausius Relationmentioning
confidence: 99%
See 3 more Smart Citations